Are Real Estate Prices Evolving into an Asset Price Bubble? - Kloppenburg, Wolfgang (ACTA VŠFS, 2021)
The development of real estate prices is of extraordinary importance for the financial and economic system, as undesirable developments could endanger financial stability – as seen in the financial crisis of 2008 and 2009. This applies not only to speculators, but also to private households, which have to borrow to pay the purchase price. The market has been “fueled” in particular by the monetary policy of the central banks – expansion of the money supply and low interest rates. Investors are looking for investment opportunities due to the money glut, and the real estate market still promises a return. Furthermore, many people looking to build are willing to go into debt to buy a property. This demand ultimately has a driving effect on real estate prices. The aim of this paper is to compare and analyze the development of real estate prices in the most important OECD countries with those of Germany. A model of real estate prices is presented, which takes into account the most important indicators and provides information on when a price bubble exists. The model shows that asset price bubbles can be identified in some OECD countries. In Germany, on the other hand, there are only signs of a price bubble in a few major cities. Since private debt is low, it does not seem to be a problem across the board in Germany. A general problem remains with regard to the timely detectability of price bubbles.